7y+9=6y+12

Simple and best practice solution for 7y+9=6y+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y+9=6y+12 equation:


Simplifying
7y + 9 = 6y + 12

Reorder the terms:
9 + 7y = 6y + 12

Reorder the terms:
9 + 7y = 12 + 6y

Solving
9 + 7y = 12 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
9 + 7y + -6y = 12 + 6y + -6y

Combine like terms: 7y + -6y = 1y
9 + 1y = 12 + 6y + -6y

Combine like terms: 6y + -6y = 0
9 + 1y = 12 + 0
9 + 1y = 12

Add '-9' to each side of the equation.
9 + -9 + 1y = 12 + -9

Combine like terms: 9 + -9 = 0
0 + 1y = 12 + -9
1y = 12 + -9

Combine like terms: 12 + -9 = 3
1y = 3

Divide each side by '1'.
y = 3

Simplifying
y = 3

See similar equations:

| 5x-4=11-x | | 3x+x=640 | | 3x+-2x+6=17 | | -5x^2+15000-1250000=0 | | 1+2+3+4+5=15 | | x+x+16=90 | | 1+2+3+4+5=55 | | 3m/2=6 | | x+16=90 | | -16t^2+30t-19=0 | | 14x+7=0 | | 0+1=100000000000 | | 2xy+20=100 | | 4x-3=8x+11 | | -1.1=1.1z+3.3 | | 16+1.6x=6.4 | | M-34=5 | | 1/5=9-2/5q | | x(5-2)=46+x | | (7x-28)+(10x-13)= | | (7x-28)+(10x-13)=180 | | f(x)=(4/x-3) | | 0,12+0,8x=-0,08 | | 4xa=40 | | (0.5)*x*80=430.8 | | x+12.36x= | | 2x^4+x^3-16x+8=0 | | (3t-8)(3t+8)=0 | | (6x+60)=9x | | 9x*2-42x+49=0 | | 3f*2-2f=1 | | 4-p/5=13 |

Equations solver categories